Diagnostic accuracy of aptamer-based biosensors for the detection of SARS-CoV-2 compared to RT-PCR: a systematic review and meta-analysis - Mohammed, Isa Haruna; Aliyu, Basiru; Sharel, Peisan E.; Amin-Nordin, Syafinaz; Chee, Hui Yee (Elsevier, 2025)
Aptamer-based biosensors present a potential alternative for the detection of SARS-CoV-2, with numerous studies demonstrating their diagnostic accuracy. A systematic review and meta-analysis are needed for evidence synthesis. A comprehensive literature search was conducted across PubMed, Scopus, Science direct, MEDLINE, as well as Embase (via Ovid) to pool articles aiming at evaluating the diagnostic accuracy of Aptamer-based biosensors in the detection of COVID-19. Using Meta-DiSc software, data from fourteen (14) included studies involving a total of 8082 clinical samples were pooled and analysed to generate a summary of the sensitivity and specificity, diagnostic odds ratio (DOR), positive and negative likelihood ratio (PLR, NLR), as well as area under the curve (AUC) of receiver operating characteristic (SROC) curve for aptamer-based electrochemical, Surface Enhanced Raman Scattering (SERS), and Enzyme Linked Oligonucleotide Assay (ELONA) and fluorescence sensing platforms. Among these platforms, the SERS demonstrated the highest diagnostic performance, with an overall 0.97 (95 % CI: 0.91–0.99) sensitivity, 0.98 (95 % CI:0.95–1.00) specificity, 766.63 (95 % CI: 133.85–4391.03) DOR and 0.98 AUC, a PLR of 33.09 (8.53–128.36) and a NLR of 0.04 (0.02–0.12). These findings underscore the high sensitivity of the SERS platform in detecting SARS-CoV-2 infection. However, the limited number of studies included in each sensing platform used for the meta-analysis restricts any generalization from the pooled data.